Optimalisasi Fungsi Masjid Untuk Keaktifan Mahasiswa - Siskandar Siskandar; Ahmad Yani (Kopertais Wilayah I DKI Jakarta dan Banten, 2020)
This research aims to analyze the function of the Kemanggisan at-Taqwa Mosque and campus mosques in terms of Worship, Education, Missionary Endeavor, Economy, Social Community, Politics, Health, Technology, Islamic Brotherhood, and Cadreization. Other objectives are the optimization of the function of the Kemanggisan at-Taqwa Mosque and several campus mosques, the transformation of mosque programs towards student activities and discovering the concept of mosque programs that are relevant to student activities.The mosque that was made the object of observation was the at-Taqwa mosque of the West Jakarta Kemanggisan Tax Complex with the consideration that the mosque is a central mosque that cooperates with 116 mosques in West Jakarta and close to 5 universities, namely: Trisakti University, Tarumanagara University, Esa Unggul University, Bina Nusantara University, and Mercu Buana University. This research period lasts from January 2019 - August 2019.This research uses a qualitative approach which is a study that uses an approach to find a deepening of symptoms that have specific substance which in this case pertains to student activities in the mosque. These findings will be analyzed using existing theories.The results of the research analysis showed that the role of students in the prosperity of the at-Taqwa mosque showed a declining trend in terms of quantity and quality and some campus mosque programs were not optimal. The author found several concept programs for students to further optimize the function of the mosque in the fields of worship, education, missionary endeavor, economics, social, political, technology, health, Islamic brotherhood and regeneration